Hexavalent chromium removal by ferrochromium slag - Erdem, Mehmet; Altundoğan, Hamdi Soner; Turan, Mehmet Deniz; Tümen, Fikret (My University, 2005)
The aim of this study is to demonstrate the potential of Cr(VI) generation during jigging operation applied for ferrochrome recovery from slag. The Cr(VI) concentrations of water contacted with ferrochromium slag (W/FS = 10) in a closed cycle after 50 batches were found as 0.61 mg/l. Also, reduction of Cr(VI) to Cr(III) and a subsequent precipitation of Cr(III) by using ferrochrome slag (FS) in a model solution has been aimed. The effects of amount of acid, contact time, FS dosage, initial Cr(VI) concentration and temperature on the Cr(VI) reduction have been studied through the batch runs. The amount of acid has been found to be the most effective parameter affecting the Cr(VI) reduction. A 10 g/l FS dosage and 3.5 ml/l H2SO4 (5 M) are sufficient to reduce all Cr(VI) in the model solution containing 10 mg/l Cr(VI) and for contact time of 60 min at 25 °C. In reduced solutions, precipitation of metal ions has been studied by using extra FS. A 60 g/l dosage of fresh FS can precipitate all Cr(III) and Fe ions in the reduced solution. Thus, it has been demonstrated that the treatment of jigging water stream to be generated in a ferrochrome plant containing Cr(VI) can be accomplished by using ferrochromium slag and sulphuric acid. Also, it has been determined that solid residues of the process are environmentally stable by applying TCLP test.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hexavalent chromium; Reduction; Ferrochromium slag; Heavy metal removal; TCLP